Low loss silica-titania waveguide films - Karasiński, Paweł; Jaglarz, Janusz; Mazur, Jacek (Photonics Letters of Poland, 2010)
The paper presents research results on two-component waveguide films SiO2:TiO2 produced in sol-gel technology. The waveguide films were deposited on soda-lime glass substrates using the dip-coating method. For the produced waveguide films, the dispersion characteristics of the refractive index and of the extinction coefficient were determined. The AFM method was used to investigate the typology of waveguide film surfaces. The attenuation of waveguide films was determined using the streak method. Full Text: PDF References: S.I. Najafi, Introduction to glass integrated optics (Boston, Artech House 1992). A.Opilski, R.Rogoziński, M.Błahut, P.Karasiński, K.Gut, Z.Opilski, "Technology of ion exchange in glass and its application in waveguide planar sensors", Opt. Engin. 36, 1625 (1997). [CrossRef] R.G.Heideman, P.V.Lambeck, "Remote opto-chemical sensing with extreme sensitivity: design, fabrication and performance of a pigtailed integrated optical phase-modulated Mach-Zehnder interferometer system ", Sens. Actuators B 61, 100 (1999). [CrossRef] C.J.Brinker, G.W.Scherer, Sol-gel science, (San Diego, Academic Press, Inc. 1990). L.C.Klein, Sol-gel optics-processing and applications (Boston, Kluwer Academic Publisher, 1994). P.Karasiński, Opt. Appl. 34, 467 (2004). P.Karasiński P., Act. Phys. Pol. A, 116, 114 (2009). F.P.Payne, J.P.R.Lacey, "A theoretical analysis of scattering loss from planar optical waveguides ", Opt. Quantum Electron. 26, 977 (1994). [CrossRef] R.R.A. Syms, Holmes, J. "Deposition of thick silica-titania sol-gel films on Si substrates", Non-Cryst. Solids 170, 223 (1994). [CrossRef]